In vitro regeneration, acclimatizationand fruit quality assessments of rockmelon (Cucumis melo) cv. Glamour / Saiyidah Nafisah Hashim - Hashim, Saiyidah Nafisah (2014)
Rockmelon cv. Glamour (Cucumis melo) is a fruit plant which belongs to Cucurbitaceae family that has great economic value, high resistance to diseases and able to produce large fruit. In this research, regeneration protocol through in vitro culture technique was developed by using different concentrations of hormones and coconut water (CW). Then, the plantlets were further acclimatized under ex vitro condition. Findings showed that nodal explants had successfully shoot regenerated on all media. In all MS media combined with CW and cytokinin, there were synergistic effects on shoot regeneration of explant. The best media for multiple shoots regenerating was obtained from MS medium combined with 0.1 mg/L kinetin and 15% CW (K0.1/15). The medium also gave the best plant growth performance with highest shoots length (2.07±1.47 cm), number of leaves (10.30±6.65) and number of nodal (2.26±1.43). In root induction media, MSO media gave the highest number of roots (10.3±2.41), root length (13.5±2.07 cm) and plantlet length (6.30±1.57 cm). For acclimatization, plantlet grown in vermiculite growth media showed the highest survival rate (81±23.09 %). Plants were further grown and fruits were harvested after 2 to 3 months. Fruit quality assessments resulted no significant differences (P>0.05) in the fruit fresh weight, fruit diameter, P-carotene and carbohydrate contents for both grown plants. In vitro grown plant did not show abnormalities which might indicate variation or mutation occurrence during the micropropagation procedures. In conclusion, direct shoot regeneration of rockmelon cv. Glamour were successfully constructed and plant had generated same quality level of fruits with in vivo grown plant.